IMPACT OF HEALTH EVOLUTION PLAN ON BETWEEN- HOSPITAL DISPATCHES OF ORTHOPEDIC SERVICE IN SHIRAZ MEDICAL SCIENCES UNIVERSITIES IN 2013-2014 - Behzadi, Babak (International Journal of Clinical and Biomedical Research, 2016)
Introduction: Today, health system, like any other event dependent to social conditions, requires effective evaluations for promoting condition and function improvement. The present study aims to examine the impact of health evolution plan on between- hospital dispatches of orthopedic service in Shiraz Medical Sciences Universities in 2013-2014. Methodology: This study was performed with descriptive- analytical method in time period of 2013 and 2014. The research population included all orthopedic service dispatches which have been accomplished from hospitals of Fars province cities to hospitals settled in Shiraz. The research sample was coincident with the mentioned statistical population. The research information was received from Shiraz Medical Sciences University, medical care monitoring center and included data relating to dispatches such as non-existence presence of specialized physician in the hospital. Statistical analysis was performed using descriptive statistics and Chi-square, Mann-Whitney test and Z-test and by SPSS 22 software. Results: The number of dispatches with average age of 41 years (SD=22/78) before health evolution plan has been 209 cases and after evolution plan it has reached 279 cases with average age of 43 years (SD=22/38). The results showed that there is a significant difference between before and after health evolution plan based on non- existence of specialist and also need to operation room (p<0.05). also, the results revealed that there is no significant difference between before and after evolution plan based on specialist presence, empty bed, department or respective service, tendency to private hospital, the patient financial problem, time of getting admission and time of admission registration (p<0.05). Conclusion: Health evolution plan has been successful in the field of specialist existence in cities while, in the field of reducing dispatches from cities to center of province has not performed successfully. Regarding the importance of between- hospital dispatch issue and expectations envisaged from evolution plan, it seems that despite the obtained changes, fundamental amendments are necessary to achieve the optimal result.